Early Mover Chasing an Opportunity: A Case Study of a Candidate of REDD+ Indonesia Project Developer - Yulianda, Yoga; Sumirat, Erman (The Indonesian Journal of Business Administration, 2013)
One of the crucial issues today faced by all of human being is climate changing. To fight with this phenomenon, some efforts are underway to overcome it. Reducing Emission from Deforestation and Forest Degradation (REDD) is one of these efforts. Business model of this approach is quite simple; who protect or upgrade forest condition should be paid. However, while other efforts have been regulated and enjoy carbon trading in the cap and trade horizon, carbon credits from REDD+ is still floating and waiting for decision from United Nations Framework Convention on Climate Change (UNFCCC), and the available market to sell REDD+ carbon is voluntary. Since it is voluntary only, then market size becomes obstacle in delivering carbon credits produced by REDD+ project type. Along with preparation of REDD+ institution in Indonesia, an early mover ready to catch the opportunity has taken an action in the middle of some uncertainties; regulation, market, price, paradigm and so on. Besides those challenges, some options exist to be chosen in creating expected value. Then this process needs management flexibility. Being involved with voluntary market only will tend to the negative Expected Net Present Value (ENPV) direction. But with the hope of incoming regulated market, ENPV is changing. This changing ENPV is merely because of wide difference on market shares. Since this hope is only 50% being occurred, handling the project cost should extend as far as possible from grant making. Along with this effort lowering Verified Emission Reduction to sell it in high quantity should be done for the first 5 to 10 years project life cycle, face it with progressive marketing strategy, and or executes conservation activities first. Free, prior, and Informed Consent becomes the guidance for project developers in engaging communities. It is valuable both for project quality enhancement and for the practical reason in upgrading VER price under Climate, Community, and Biodiversity Alliance.Key Words: Climate Change, REDD+, Carbon Finance, Real Options Analysis (ROA), Stakeholder Analysis